An Effect of Planning, Organizing, Staffing, Leading and Controlling of Operational Leadership - Ikhah Malikhah (Budapest International Research and Critics University, 2021)
This study aims to examine and analyze the influence of planning, organizing, staffing, leading, controlling on operational leadership at the Universitas Pembangunan Panca Budi Medan, as well as testing the effect of planning, organizing, staffing, leading, controlling simultaneously and partially on operational leadership and the variables involved. The dominant influence on operational leadership at the University of Development Panca Budi Medan. The method used is multiple regression analysis (Multiple Regression) through the stages of testing the classical assumption data instrument test and hypothesis testing. Instrument data is measured through a questionnaire distributed to respondents. The results showed that the five variables simultaneously and partially had a significant effect on operational leadership at the Universitas Pembangunan Panca Budi Medan. The most dominant variable is planning compared to leading, controlling, organizing, staffing variables.